Cardiac Rehabilitation and Risk Reduction - Sandesara, Pratik B.; Lambert, Cameron T.; Gordon, Neil F.; Fletcher, Gerald F.; Franklin, Barry A.; Wenger, Nanette K.; Sperling, Laurence (Journal of the American College of Cardiology, 2015)
Atherosclerotic cardiovascular disease (ASCVD) continues to increase annually in the United States along with its associated enormous costs. A multidisciplinary cardiac rehabilitation (CR) and risk reduction program is an essential component of ASCVD prevention and management. Despite the strong evidence for CR in the secondary prevention of ASCVD, it remains vastly underutilized due to significant barriers. The current model of CR delivery is unsustainable and needs significant improvement to provide cost-effective, patient-centered, comprehensive secondary ASCVD prevention.